STRATEGY TO INCREASE HR PRODUCTIVITY THAT USES COWORKING SPACE AS A NEW WORKPLACE CONCEPT IN MEDAN CITY - Muhammad Habibie; Iskandarini; Yeni Absah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The number of freelancers and start-up companies in Indonesia has increased from year to year, which has led to the emergence of new work styles (new work orders), where this work style has characteristics that are more free, flexible and independent, even the problems that arise are different from the work model in general. This needs to be supported by the availability of a place to work, one of the alternative places to work that is currently developing is coworking space. Even though the development of coworking spaces continues to increase, community participation in coworking spaces in the city of Medan is not yet optimal, and people even tend to equate cafés and coffee shops as coworking spaces. Research was carried out on CoHive at Clapham, Cohub Indonesia, Cradle Event & Coworking Space, SAGA Creative Hub, and Digital Innovation Lounge Medan. The analytical method used in the research is a Likert scale to measuring the opinions and perceptions of a person or group and Multiple Linear Regression to look at the factors that influence person or group using co working space. The reseach results show that Physical environmental factors that influence the productivity of human resources working in Co Working Space are lighting, noise and cleanliness. Non-physical environmental factors that influence the productivity of human resources working in Co Working Space are attention and support from leaders, collaboration between groups, and communication. SOAR analysis in determining strategies for increasing human resource productivity using co-working space, namely: S-A Strategy: Modern and comfortable facilities, location accessibility, flexibility in work space choices, and an atmosphere that supports creativity as well as better collaboration, opportunities to develop professional networks, or increase work focus. O-A Strategy: There are networking events, workshops or seminars on relevant topics, or collaborative projects with companies or other professionals in the co-working space and users can improve specific skills, expand their business network, or achieve a better balance between personal and professional life. S-R Strategy: Users can increase work productivity, innovation in business ideas, or increase job satisfaction and have the opportunity to increase their income, work efficiency, product or service quality. O-R Strategy: Users get access to business acceleration programs, funding, or joint projects with large companies that partner with the co-working space and users have the opportunity to increase market share